Taxonomy of free-living marine nematodes (nematoda) in Sarawak Coastal Waters - Norliana i., Binti Mohd Rosl (Universiti Malaysia Sarawak (UNIMAS), 2011)
A taxanomic study on free-living nematodes had been carried out in Saawak coastal waters to clarify the systematic and distribution of nematodes in Saawak. This is the first taxanomic study conducted in Saawak. The aim of the present study is to establish the database for marine nematodes in Sarawak. The sampling was carried out at 24 study sites along the coastal waters of Saawak covers the interdal and subtidal area. Three replicates of marine sediment were taken and sieved in-situ using seawater with a 500um sieve above and 45um sieve below befoe preserved in the specimen bottle with 5% buffered formalin. In the laboratory, the nematodes specimen wee processed, mounted and identified.